2011
DOI: 10.1007/s00436-011-2501-6
|View full text |Cite
|
Sign up to set email alerts
|

Species diversity and geographic distribution of hard ticks (Acari: Ixodoidea: Ixodidae) infesting domestic ruminants, in Qazvin Province, Iran

Abstract: This report presents the results of the first faunistic study of hard ticks in Qazvin province of Iran. The primary objective was to determine the species diversity and geographic distribution of hard ticks that parasitize domestic ruminants. Information about the abiotic preferences of these species has been provided. A total of 286 cattle, 1,053 goats, and 2,050 sheep were examined in 13 villages in 28 flocks distributed throughout the studied areas. Total direct body collections of ticks were made from each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 15 publications
7
22
0
Order By: Relevance
“…This was in agreement with studies which demonstrated that H. asiaticum was the second abundant tick infesting sheep (48.5%) in south Khorasan province and H. anatolicum was the most frequent species with 71.5% of the ticks of Domestic Ruminants in the Southern Khorasan-e-Razavi province, Iran [17] [18]. In a recent investigation in Iran, H. anatolicum and H. asiaticum were found with a prevalence of 5.9% and 3.9% respectively, in mountainous areas of Golestan province, north of Iran [12]; a similar prevalence was reported in investigations in Mazandaran Provice (north of Iran) and Yazd province (center of Iran) [2] [19], whereas H. anatolicum was the infrequent species with prevalence of 0.4% among collected species in Qazvin province [10]. We collected Hy.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This was in agreement with studies which demonstrated that H. asiaticum was the second abundant tick infesting sheep (48.5%) in south Khorasan province and H. anatolicum was the most frequent species with 71.5% of the ticks of Domestic Ruminants in the Southern Khorasan-e-Razavi province, Iran [17] [18]. In a recent investigation in Iran, H. anatolicum and H. asiaticum were found with a prevalence of 5.9% and 3.9% respectively, in mountainous areas of Golestan province, north of Iran [12]; a similar prevalence was reported in investigations in Mazandaran Provice (north of Iran) and Yazd province (center of Iran) [2] [19], whereas H. anatolicum was the infrequent species with prevalence of 0.4% among collected species in Qazvin province [10]. We collected Hy.…”
Section: Discussionsupporting
confidence: 73%
“…There are several reports on epidemiology, distribution, medical importance and susceptibility of different ticks through the country [2] [5]- [9]. The occurrence of nine ixodid tick species was determined from Qazvin province, Iran [10].…”
Section: Introductionmentioning
confidence: 99%
“…Ixodid ticks are obligatory blood-sucking ectoparasites of various mammals, birds, reptiles, and amphibians [3] and vectors of different agents of diseases in both man and livestock [4,5] . There are several reports on host preference, infectivity, geographical distribution, insecticide resistance, molecular detection of different organisms, biodiversity, seasonal activity, classification, fauna, ecology and biology of hard and soft ticks which have been investigated by various researchers in the country [6][7][8][9][10][11][12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…It covers roughly 4992 km 2 and lies within the longitude 48 • 58 to 50 • 51 E and latitude 36 • 08 to 36 • 48 N. In the northern watersheds of Qazvin, the Shahrood river flows, which is the result of joining Taleghan and Alamut rivers [39]. Due to the presence of the Alborz mountains, this area is known to have a mountainous climate [40], and approximately half of the area is covered by mountainous pastures. The altitude ranges from 239 to 4093 m above the sea level, and it is higher than 1200 m in the major part of the area [4].…”
Section: Study Areamentioning
confidence: 99%
“…The average temperature of the hot and cold seasons is reported as approximately 28 • C and 1 • C, respectively. Also, the annual precipitation in most parts of the county is higher than 500.5 mm [40]. The slope ranges from 0 • to 45 • , where more than 70% of the area contains gentle slopes (i.e., slope lower than 15 • ).…”
Section: Study Areamentioning
confidence: 99%